BELL Y DEPTH STUDIES FOR SHRIMP TRAWLS 8 PART II - MHALATHKAR, H N.; JAGADEESHAN, G (Fishery Technology, 2025)
The paper details further experiments conducted for a reduction in the depth of belly of a 13.69 m (45’) four seam shrimp trawl net. The investigations have given conclusive evidence that the optimum depth of belly for this particular trawl design should be 70 meshes.